INTERRELATIONSHIP OF INTERLEUKIN-17F (IL-17F) SINGLE NUCLEOTIDE POLYMORPHISM (RS763780) WITH SUSCEPTIBILITY TO HELICOBACTER PYLORI INFECTION (The Research of Medical Science Review, 2025)
Helicobacter pylori infection is caused by Gram negative bacteria that enters the body and lives in the digestive tract. The bacterium is responsible for causing ulcers in the lining of the stomach and can lead to stomach cancer. Many genetic and environmental factors are involved in the onset and severity of the H. pylori infection. This study was designed to identify the association of Single Nucleotide Polymorphism (SNP) rs763780 in the IL-17F gene with the H. pylori infection. Total 120 samples were taken, including 60 H. pylori infected patient samples and 60 healthy individual samples. DNA was extracted from the blood samples using Organic Phenol Chloroform method. The extracted DNA was genotyped using Tri-primer PCR method. From genotyping analysis, it was found that TT genotype was greater in controls samples as compared to infected individuals and CT genotype was found greater in infected individuals’ samples than in control samples. Similarly, in case of allelic frequency, C allele frequency was greater in cases as compared to control samples. From results it was concluded that C allele significantly increased the risk of getting H. pylori infection and polymorphism in IL-17F (T>C) can be possibly involved in the susceptibility to H. pylori infection.